Cross-cultural adaptation of the medical engagement scale into Danish general practice setting. (3rd April 2019) - Ahnfeldt-Mollerup, Peder; Riisgaard, Helle; Søndergaard, Jens; Nexøe, Jørgen
Abstract: Introduction: The need to involve doctors in healthcare leadership has long been recognized by clinical staff and policymakers. A Medical Engagement Scale has been designed in England to evaluate levels of medical engagement in leadership and management. Objective: The aim of this study was to translate and adapt the scale and to test the translated version for comprehension and suitability in Danish general practice setting. Design and method: The process involved forward translation, backward translation, and field tests. The field tests included cognitive debriefing interviews. In all 30 general practitioners and 5 non-general practitioners participated in the process of translation. After using the scale among 1652 general practitioners statistical analysis was carried out to test internal consistency. Setting: The study was carried out in general practice in Denmark. Results: Several changes made during the process in order to achieve a Danish version that is acceptable, understandable and still capable of measuring medical engagement comparable of the original English version. Analysis of scale internal consistency using Cronbach's alpha revealed acceptable reliability for all three meta-scales, which ranged from 0.69 to 0.81. The overall tool achieved a Cronbach's alpha of 0.89. Conclusion: The Danish version of the Medical Engagement Scale is a valid and reliable tool that is acceptable and relevant for general practice in Denmark. Key points: This study describes the cross-cultural adaptation of the Medical Engagement Scale from a UK primary healthcare setting to a Danish primary healthcare setting. The process produced a relevant and acceptable questionnaire measuring medical engagement. Internal consistency revealed acceptable reliability The translation of the scale provides the possibility to use this scale for practical and academic purposes.